The impact of physical distancing on socially vulnerable people needing care during the COVID-19 pandemic in the Netherlands. (5th February 2022) - de Vries, Daniel; Pols, Jeannette; M'charek, Amade; van Weert, Julia
Abstract : What was the impact of physical distancing on socially vulnerable groups needing care during the first COVID-19 pandemic lockdown in the Netherlands? We conducted repeated qualitative interviews with 141 people in care relationships and 106 professionals, and two repeated surveys among older populations outside ( n = 1697) and inside long-term care facilities ( n = 2619). Findings show a diversity of experiences, ranging from relative calmness and feeling socially normal, to loneliness and loss of perspective. Care must be seen as essential social traffic needed to guarantee basic quality of life for these groups during disease outbreaks. Findings emphasise an empirical ethics approach to policy interventions.